Taksiran Total Fertilitas Rate Penduduk Jabar Periode 2015 - 2020 dan 2020 - 2025 - Monika Rizki; Yayat Karyana (Jurnal Riset Statistika, 2022)
Abstract. The population problem in Indonesia is a fairly important problem considering the number of Indonesians who are in fourth place as the country with the largest population. The case study is estimating the TFR figure and the population of West Java Province for the 2015 - 2020 period and a literature study studying the literature on basic theories related to population growth problems related to vital events, namely fertility. The data analysis technique used in this research is the indirect method. Based on the results of SP 2020, the population of West Java aged 0-4 years, there are 2,004,029 men and 1,910,514 women. With the number of births during these 5 years, the calculation results produce an estimated TFR of the population of West Java in the 2015 - 2020 period is TFR = 2.12. Based on the projections for 2025, the population of 0-4 years is 1,957,026 women and 2,045,940 men, with the total number of men and women being 4,002,966. With the number of births during these 5 years, the calculation results produce an estimated TFR of the population of West Java in 2020 - 2025 is TFR = 2.12. Abstrak. Permasalahan kependudukan di Indonesia menjadi masalah yang cukup penting mengingat jumlah penduduk Indonesia yang berada pada urutan keempat sebagai negara dengan jumlah penduduk terbesar. Studi kasus yaitu memperkirakan angka TFR dan jumlah penduduk Provinsi Jawa Barat periode 2015 - 2020 dan studi literatur mempelajari pustaka tentang teori dasar yang berkaitan dengan permasalahan pertumbuhan penduduk yang berhubungan dengan peristiwa vital yaitu fertilitas. Teknik analisis data yang digunakan dalam penelitian ini adalah metode tidak langsung. Berdasarkan hasil SP 2020 penduduk Jawa Barat berumur 0-4 tahun terdapat 2.004.029 orang laki-laki dan 1.910.514 orang perempuan. Dengan banyaknya kelahiran selama 5 tahun tersebut, hasil perhitungan menghasilkan perkiraan TFR penduduk Jawa Barat pada tahun periode 2015 – 2020 adalah TFR=2,12. Berdasarkan hasil proyeksi tahun 2025 penduduk 0-4 tahun terdapat 1,957,026 orang wanita dan 2,045,940 orang laki-laki dengan jumlah keseluruhan laki-laki dan perempuan adalah 4,002,966 orang. Dengan banyaknya kelahiran selama 5 tahun tersebut, hasil perhitungan menghasilkan perkiraan TFR proyeksi penduduk Jawa Barat pada tahun 2020 - 2025 adalah TFR=2,12.